Winchester Cathedral
Flying buttresses on the outside of the choir at Winchester show that it was intended to erect a stone vault to complete the work of improvement. However, in the event a wooden lierne vault was built instead, with fine colored bosses, and it is now restored, with the arms and badges of Lancastrian and Tudor families. The form of the vault has affinities with fan vaulting.